Knowledge, Perspectives, and Priorities Regarding Self-Care Activities: A Population-Based Qualitative Study among Iranian Adolescents - Marjan Mohammadzadeh; Tayebe Alizadeh; Hamidin Awang; Zahra Mohammadzadeh; Frahnaz Mirzaei; Christiane Stock (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
This qualitative study aimed to investigate knowledge, perspectives, and priorities related to self-care among Iranian adolescents. Through snowball sampling, the link to the questionnaire was shared in available social media apps. The results showed that 192 of 294 participants reported that they had heard about “self-care”. Parents/family and school were the most frequent sources of learning about self-care among the male and female respondents, respectively. Analyzing the participants’ statements regarding their own understanding of self-care activities, three major terms—“taking care of”, “avoid”, and “respect” were identified. When being ask about what they do for their own self-care, the results showed spending time on the Internet had the highest repetition rate among boys’ responses, followed by “going to gym”, “video games”, and “listening to music”. Regarding the desired activities, both girls’ and boys’ statements indicated that among leisure activities, “traveling” was the most frequent word, followed by being with friends. The girls showed more interest in attending night clubs or spending time outside the home late at night. Insights from this study identifying preferences in self-care activities can be used to develop intervention programs for Iranian adolescents to improve their lifestyle and, consequently, their well-being based on their needs and situation.